The spatial and temporal effect on the phytochemicals of Dodonaea viscosa var. angustifolia (L.f.) Benth - Marx, Jan-Taljaard (Stellenbosch : Stellenbosch University, 2021)
Thesis (MSc)--Stellenbosch University, 2021.